Destroying glutathione peroxidase improves the oxidative stress resistance and pathogenicity of Listeria monocytogenes - Zhang, Yu; Guo, Qian; Fang, Xiaowei; Yuan, Mei; Hu, Wenjie; Liang, Xiongyan; Liu, Jing; Yang, Yuying; Fang, Chun (Frontiers in Microbiology, 2023)
Glutathione peroxidase is abundant in eukaryotes as an important antioxidant enzyme. However, prokaryotic glutathione peroxidase has not been thoroughly studied. Listeria monocytogenes is a facultative intracellular pathogen that is capable of causing listeriosis in animals as well as humans. Despite the fact that L. monocytogenes encodes a putative glutathione peroxidase, GSH-Px (encoded by lmo0983), the functions of the enzyme are still unknown. Here we revealed the unusual roles of L. monocytogenes GSH-Px in bacterial antioxidants and pathogenicity. Deficiency of GSH-Px not only increased glutathione concentrations in L. monocytogenes but also enhanced its resistance to oxidative stress when exposed to copper and iron ions. In addition, the absence of gsh-px significantly improved the adhesion and invasion efficiency of L. monocytogenes to Caco-2 cells. More importantly, L. monocytogenes lacking GSH-Px could colonize and proliferate more efficiently in mice livers and spleens, enhancing the pathogenicity of L. monocytogenes by increasing the expression of virulence factors like InlA, InlB, and LLO. Taken together, we confirmed that GSH-Px of L. monocytogenes has a counter-intuitive effect on the antioxidant capacity and pathogenicity.